Increased thrombin generation and platelet activation are associated with deficiency in high molecular weight multimers of von Willebrand factor in patients with moderate-to-severe aortic stenosis. Issue 24 (10th May 2011) - Natorska, Joanna; Bykowska, Ksenia; Hlawaty, Marta; Marek, Grzegorz; Sadowski, Jerzy; Undas, Anetta
Abstract : Background: High molecular weight von Willebrand factor (vWF) multimers (HMWM) are often deficient in patients with severe aortic stenosis (AS) owing to shear stress-enhanced proteolysis of vWF. It has also been reported that AS is associated with increased activation of blood coagulation. Objective: To investigate whether patients with AS with a deficiency in vWF HMWM have enhanced thrombin generation and platelet activation in vivo. Design: Based on the analysis of vWF HMWM performed using immunolocalisation, 11 subjects with vWF HMWM deficiency (low %HMWM group) were identified and compared with 42 patients with AS with a normal distribution of vWF HMWM (normal %HMWM group). Plasma thrombin markers thrombin-antithrombin complexes (TAT) and prothrombin factor 1+2 (F1.2) plus platelet activation markers soluble CD40 ligand (sCD40L), β-thromboglobulin and P-selectin were also measured. Patients: 48 consecutive patients with severe AS and five with moderate AS, free of angiographically-proven coronary artery disease and clinically overt bleeding, were studied. Results: Patients in the low %HMWM group had 34.8% higher maximal transvalvular gradient (p=0.0003) and 44.8% higher mean gradient (p=0.0002) than those in the normal %HMWM group. Thrombin formation was enhanced in the low %HMWM group (F1.2, 284.5±63.7 vs 216.9±62.5 pmol/l, p=0.004; thrombin-antithrombin, 4.89±1.3 vs 4.06±0.9 μg/l, p=0.02) and both markers showed inverse correlations with the percentage of vWF HMWM (r=−0.59, p=0.002; r=−0.42, p=0.03, respectively). In the low %HMWM group sCD40L (279.4±60.7 vs 221.4±41.7 pmol/l, p=0.003) and β-thromboglobulin (73.1±9.2 vs 64.5±8.5 IU/ml, p=0.04), but not P-selectin, were also higher than in the remaining patients with AS. Conclusion: Patients with advanced AS deficient in vWF HMWM are characterised by enhanced thrombin formation and platelet activation. This observation indicates the ambivalent impact of high shear stress in AS on haemostasis and might help explain two aspects of AS—Heyde syndrome and increased risk of thromboembolism.